Improving particle collection efficiency of sampling wipes used for trace chemical detection. Issue 5 (7th January 2022) - Gillen, Greg; Lawrence, Jeffrey; Sisco, Edward; Staymates, Matthew E.; Verkouteren, Jennifer; Robinson, Elizabeth L.; Bulk, Alexander
Abstract : Simple modification of sampling wipes improves the collection efficiency of explosive particles for trace chemical detection. Abstract : Improvement of the particle collection efficiency of sampling wipes is desirable for optimizing the performance of many wipe-based chemical analysis techniques used for trace chemical screening applications. In this note, commercially available Teflon coated fiberglass and calendered Nomex sampling wipes were modified by mechanically scoring the wipe surface to produce topography that promoted enhanced and localized particle collection. Wipe surface modifications improved particle collection efficiency, relative to unmodified wipes, by factors of 3 to 13 depending on sampling conditions, wipe type, and surface sampled. Improvements were demonstrated for both model polystyrene latex microspheres and inkjet printed explosive particles. The modifications also concentrated particles into pre-defined locations on the wipe which can be engineered to ensure maximum overlap with the thermal desorber of a trace contraband detection system allowing for more effective analysis of collected trace residues.